Sexual and Reproductive Health Needs and Priorities of the Adolescents in Northern Pakistan: A Formative Evaluation - Salima Meherali; Komal Abdul Rahim; Zohra S. Lassi (MDPI AG, 2022)
The vast majority (90%) of the world's young people aged 10-24 years live in low and middle-income countries (LMICs). Pakistan has one of the world's largest populations under 30 years. Adolescents' access to basic sexual and reproductive health (SRH) services, such as family planning and sexuality education, remains low, especially in rural areas such as the Gilgit-Baltistan (GB) province of Northern Pakistan. This study addressed these gaps by exploring the SRH priorities and health information needs of adolescents living in GB. A cross-sectional survey was conducted with adolescents and healthcare providers. A total of 216 adolescents and 22 healthcare providers completed the survey forms. The findings pointed out that adolescents in GB have unmet SRH needs and are more interested in learning about SRH, human immunodeficiency virus (HIV) and sexually transmitted infections (STIs), and sexual abuse. The majority of the participants highlighted that their age, fear of being judged/stigmatized, and society's attitude toward sex hinder them from opting for SRH services. The majority of healthcare providers reported that they are not well-equipped to tackle SRH-related issues and require training to better serve the adolescent SRH needs. The findings from this study have highlighted that there is a need to formulate robust interventions and strategies to raise knowledge and awareness about SRH needs among adolescents.